The Public–Private Dichotomy in Fascist Corporativism: Discursive Strategies and Models of Legitimization - Cau, Maurizio (2017)
The twentieth century starts with a rediscovery of the collective dimension that legal modernity had compressed. The vivid debate that came with the fascist corporatist experiment is an interesting observatory that lets us read this process against the light. According to the major part of Italian legal culture the corporatist cultural project seems to forewarn a new framework of the connections between public and private spheres, state and society, law and economics, statism and pluralism. Corporatism, which did not intend to build a non-statual model of authority, was an answer to the need to attribute legal value and legal autonomy to economic and social actors that weren’t adequately represented in the political and normative circuit. The paper is aimed at retracing some of the discursive strategies that characterized the corporatist experiment and the different legitimization models that were proposed by legal theory in order to rebuild the dichotomy between public and private spheres.